An Anthropometric study on facial index in chronic sinusitis patients of Raichur district, Karnataka - V Ravivarma; R S Bulagouda; N S Naveen; U Venkatesh; Sandhya (Wolters Kluwer Medknow Publications, 2020)
Back ground: Anthropometry of facial analysis is very useful in recognition of racial, ethnical, sexual differences and reconstructive surgery of individuals. Aim: In the present study, we aimed to determine the facial index in chronic sinusitis patients of Raichur district, Karnataka through anthropometric study. Objective: To study the facial index in chronic sinusitis patients. Materials and Methods: It is an observational descriptive study done in Anatomy department, RIMS, Raichur which was performed on 24 individuals (13 males & 11 females) aged between 18- 60 years of chronic sinusitis patients. Patient are taken to the radio-diagnosis for Computerized tomography (CT) evaluation & to measure the facial index. Formula for facial index is morphological facial height is measured with caliper scale from nasion to gnathion & facial width is measured as straight distance between the right and left zygions. Results: Facial index was calculated according to the formula and the results obtained were analyzed statistically using the Chi-square test. The highest type of face in chronic sinusitis observed in euryprosopic & hyperleptoprosopic faces (29%) and least type is hypereuryprosopic faces (4%). Conclusion: There is a significant relation of the facial index observed in hypereuryprosopic & leptoprosopic.